2007
DOI: 10.1126/science.1145447
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Transverse Magnetohydrodynamic Waves in a Solar Prominence

Abstract: Solar prominences are cool 10(4) kelvin plasma clouds supported in the surrounding 10(6) kelvin coronal plasma by as-yet-undetermined mechanisms. Observations from Hinode show fine-scale threadlike structures oscillating in the plane of the sky with periods of several minutes. We suggest that these represent Alfvén waves propagating on coronal magnetic field lines and that these may play a role in heating the corona.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
411
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(442 citation statements)
references
References 23 publications
28
411
3
Order By: Relevance
“…Ion cyclotron heating and the turbulent cascade models exploit the notion that low frequency shear Alfven waves excited in the chromosphere will survive into the lower corona. Upward propagating Alfven modes have been observed in the chromosphere (de Pontieu et al 2007), in the lower corona by Hinode (Ofman and Wang 2007;Okamoto et al 2007) and by ground-based detectors (Tomczyk et al 2007). The ion cyclotron heating mechanism proceeds by resonant wave particle interactions with Alfven waves, leading to heating of the solar corona (Isenberg 2001b(Isenberg , 2004.…”
Section: Heating the Corona And Solar Windmentioning
confidence: 99%
“…Ion cyclotron heating and the turbulent cascade models exploit the notion that low frequency shear Alfven waves excited in the chromosphere will survive into the lower corona. Upward propagating Alfven modes have been observed in the chromosphere (de Pontieu et al 2007), in the lower corona by Hinode (Ofman and Wang 2007;Okamoto et al 2007) and by ground-based detectors (Tomczyk et al 2007). The ion cyclotron heating mechanism proceeds by resonant wave particle interactions with Alfven waves, leading to heating of the solar corona (Isenberg 2001b(Isenberg , 2004.…”
Section: Heating the Corona And Solar Windmentioning
confidence: 99%
“…2. Prominence plasma is predominantly dynamic, exhibiting horizontal and/or vertical motions of order 10-70 km s −1 (Kubota and Uesugi, 1986;Zirker et al, 1998a;Kucera et al, 2003;Lin et al, 2003;Okamoto et al, 2007;Chae et al, 2008). Quiescent filaments can go through phases of enhanced internal motion and activity (Martin, 1973;Tandberg-Hanssen, 1995;Kucera et al, 2006), altering the amount of cool material in the filament (Kilper et al, 2009).…”
Section: Plasma Structure and Dynamicsmentioning
confidence: 99%
“…High-resolution Hα and Ca II H observations of prominences have recently been obtained with the Solar Optical Telescope (SOT) on the Hinode Satellite. Okamoto et al (2007) observed horizontal threads in a prominence near an active region and studied the oscillatory motions of these threads. A movie of the evolution of these threads may be seen in Okamoto et al (2007).…”
Section: Basic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Locally, they consist of fine and vertically oriented plasma structures, so-called threads, that evolve continually (e.g., Engvold 1976;Zirker et al 1994). Recent ob-A movie is available in electronic form at http://www.aanda.org 1 There are many papers about solar prominences, but we recommend that the reader first go through the historical work of Einar Tandberg-Hanssen (e.g., Tandberg-Hanssen 1998, 2011 servations taken with the Hinode satellite have revolutionized our knowledge of the fine-scale structuring and dynamics of quiescent prominences; for instance, plasma oscillations, supersonic downflows, or plasma instabilities like the Rayleigh-Taylor instability in prominence bubbles (Berger et al 2008(Berger et al , 2010Chae et al 2008;Okamoto et al 2007). …”
Section: Introductionmentioning
confidence: 99%